Nanoparticle-Integrated Hydrogels as Multifunctional Composite Materials for Biomedical Applications - Biondi, Marco (Gels, 2015)
This review focuses on the most recent developments in the field of nanocomposite hydrogels intended for biomedical applications. Nanocomposite hydrogels are hydrated polymeric networks with a physically or covalently crosslinked three-dimensional (3D) structure swollen with water, in the presence of nanoparticles or nanostructures. A wide array of nanomaterials (polymeric, carbon-based, metallic, ceramic) can be incorporated within the hydrogel network to obtain reinforced nanocomposite hydrogels. Nanocomposites represent a new class of materials with properties absent in the individual components. In particular, the incorporation of nanomaterials within a polymeric hydrogel network is an attractive approach to tailor the mechanical properties of the hydrogels and/or to provide the nanocomposite with responsiveness to external stimuli.